2018
DOI: 10.1111/ejn.13985
|View full text |Cite
|
Sign up to set email alerts
|

The strengths of the genetic approach to understanding neural systems development and function: Ray Guillery's synthesis

Abstract: The organization and function of sensory systems, especially the mammalian visual system, has been the focus of philosophers and scientists for centuries-from Descartes and Newton onward. Nevertheless, the utility of understanding development and its genetic foundations for deeper insight into neural function has been debated: Do you need to know how something is assembled-a car, for example-to understand how it works or how to use it-to turn on the ignition and drive? This review addresses this issue for sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Many of them are remembrances of Ray as mentor and role model, with reference to his lively discussion and debate over the issues that fascinated him. Three remembrances were contributed by his trainees: Anthony LaMantia () and Chris Walsh (), who were students during Ray's last period until 1985 in the US at the University of Chicago, and one of us (CAM) (Mason, ), who was his postdoctoral fellow during this time (see above). This latter article is the most unusual, because the reminiscences are blended with Ray's own story of how he discovered a path to albinism through his serendipitous finding of aberrations in the path from eye to brain in the Siamese cat.…”
Section: This Issuementioning
confidence: 99%
“…Many of them are remembrances of Ray as mentor and role model, with reference to his lively discussion and debate over the issues that fascinated him. Three remembrances were contributed by his trainees: Anthony LaMantia () and Chris Walsh (), who were students during Ray's last period until 1985 in the US at the University of Chicago, and one of us (CAM) (Mason, ), who was his postdoctoral fellow during this time (see above). This latter article is the most unusual, because the reminiscences are blended with Ray's own story of how he discovered a path to albinism through his serendipitous finding of aberrations in the path from eye to brain in the Siamese cat.…”
Section: This Issuementioning
confidence: 99%
“…Ray and I had many detailed discussions about early thalamocortical development. Ray had shown that the sensory periphery and the central thalamocortical and corticothalamic pathways started their development separately and they only interacted at later stages (Mitrofanis & Guillery, ; see papers by Lamantia, and Walsh, in this issue). Therefore, the early stages of thalamocortical development take place autonomously, with the sensory periphery plugging into these immature circuits before beginning to transmit spontaneous and later sensory information.…”
Section: Men In the Machinementioning
confidence: 99%
“…The latter question was Ray's focus. The articles in this issue by Murray Sherman, Anthony LaMantia, Zoltan Molnár, Jeremy Taylor, and Chris Walsh also touch on Ray's pioneering approach to linking genes, circuits, and behavior (Sherman, ; LaMantia, ; Molnar, ; Taylor, ; Walsh, ). And for additional reviews on the albino, see Jon Kaas’ excellent narrative of Ray's discovery (Kaas, ), and comparisons of the albino rodent and human visual systems (Jeffery, ) and of the albino, achiasmatic, and pigmented visual systems (Prieur & Rebsam, ).…”
Section: Introductionmentioning
confidence: 99%